Potencial biológico de bactérias cultiváveis de Aedes aegypti (Linnaeus, 1762) da biota Amazônica, ativas contra este vetor - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
The bacterial microbiota associated with mosquitoes is diverse and can interact symbiotically or antagonistically with their hosts, providing an alternative in the search for new entomopathogenic agents. In this study, cultivable bacteria isolated from all life stages of Ae. aegypti were analyzed for: i) their larvicidal activity of crude metabolites and determination of LC50 and LC90 against Ae. aegypti; ii) taxonomic identification of the bacteria, involving morphological and molecular analyses; and iii) larvicidal activity of cellular components (pellet) and supernatants obtained from Enterobacter spp., Bacillus spp., and Stenotrophomonas spp. against Ae. aegypti. For topic i, 424 bacteria were isolated from egg, larva, pupa, and adult female samples of Ae. aegypti using culture media (NA, LB, and ISP2). All bacteria were tested for entomopathogenic potential against larvae of this vector. Nine strains of the genera Bacillus, Enterobacter, and Stenotrophomonas showed 100% larvicidal activity, similar to the standard strain Bti AM65-52. Regarding topic ii, among 415 isolates analyzed for bacterial diversity, 300 are Gram-negative and 115 Gram-positive. All strains were catalase positive and presented ten morphotypes: negative coccus, positive bacillus, negative bacillus, negative coccobacillus, positive microbacillus, negative microbacillus, positive cocci, negative micrococcus, negative diplococcus, and positive coccobacillus. The strains were grouped according to morphological characteristics, where a representative of each group was identified by molecular characters. Through 16S rRNA gene sequencing, 68 bacterial strains were sequenced, and their sequences were compared with those in GenBank. The identified genera were: Acinetobacter, Bacillus, Delftia, Enterobacter, Leclercia, Pseudomonas, Paenibacillus, Stenotrophomonas, and Sphingobacterium, representing three phyla. The phylum Proteobacteria (60.30%) was the most abundant, followed by Bacillota (36.76%) and Bacteroidetes (2.94%). Regarding topic iii, nine strains that exhibited larvicidal activity were used to test the fractions of secreted supernatant and cellular components (pellets) for larvicidal activity. The results demonstrated that the pellet fraction of bacteria P18NA-Enterobacter sp. and L65NA-Bacillus sp. caused 100% larval mortality within the first 24 hours, respectively. Regarding the toxicity of the secreted supernatant fraction, the bacterium P18NA- Enterobacter sp. caused 100% mortality in 24 hours, while the strain L65NA-Bacillus sp. achieved 98% within 72 hours. The pellet and supernatant fractions of the strains presented toxicity profiles similar to the Bti AM65-52 strain. Therefore, this study demonstrates that some bacteria isolated from Ae. aegypti may exhibit antagonistic potential towards the vector itself. The data are promising for the development of new bioinsecticides for the control of these medically important mosquitoes. Additionally, this study provides new information on the structure and abundance of microbiota at different stages of Ae. aegypti and an understanding of the interactions between mosquitoes and microorganisms.
Keywords: Aedes aegypti - Controle; Mosquitos - Controle; CIENCIAS DA SAUDE: SAUDE COLETIVA: SAUDE PUBLICA; OUTROS; Microbiota bacteriana; Metabolismo; Aedes aegypti; Vetor; Controle biológico